2022
DOI: 10.34108/eujhs.928190
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Level of Breast Cancer and Health Beliefs of Health Professionals

Abstract: Amaç: Bu çalışma, hemşire, ebe ve acil tıp teknisyenlerinin meme kanseri risk düzeyini ve bu kanserin erken tanılanmasına yönelik sağlık inançlarını belirlemek amacıyla yapılmıştır. Yöntem: Tanımlayıcı tipteki bu çalışma, bir üniversitenin araştırma ve uygulama hastanesinde görev yapan 146 hemşire, ebe ve acil tıp teknisyeni ile gerçekleştirilmiştir. Araştırmanın verileri, “Veri Toplama Formu”, “Meme Kanseri Risk Değerlendirme Formu” ve “Meme Kanseri Sağlık İnanç Modeli Ölçeği (MKSİMÖ)” kullanılarak topl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…To increase women's participation in early screening programmes, women's awareness of gynaecological cancer should be raised first (Kıyak and Burucu, 2022;Teskereci et al, 2020). High awareness of early screening programmes reduces cancer-related morbidity and mortality rates (Efe Arslan et al, 2022;Sahin, 2015;Durmaz et al, 2021). Women's health perceptions affect their health-related behaviours and health responsibilities (Ozdelikara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To increase women's participation in early screening programmes, women's awareness of gynaecological cancer should be raised first (Kıyak and Burucu, 2022;Teskereci et al, 2020). High awareness of early screening programmes reduces cancer-related morbidity and mortality rates (Efe Arslan et al, 2022;Sahin, 2015;Durmaz et al, 2021). Women's health perceptions affect their health-related behaviours and health responsibilities (Ozdelikara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization’s 2020 report, breast cancer affected 2.3 million women, resulting in 685,000 fatalities. 1 - 8 …”
mentioning
confidence: 99%
“…Patients should be informed about the use of fragrancefree soaps; avoidance of cosmetics such as deodorants, perfumes and powders on the skin; recommendation of loose cotton clothing that absorbs sweat and does not irritate; avoidance of tight clothing such as belts and bras; and avoidance of hot applications such as hot thermophoresis and electric blankets. [1][2][3]11,12 The study found that the majority of patients were informed on the disease and treatment options, but were not aware of the side effects of these treatments. In addition, skin assessments showed that while the incidence of skin sensitivity, discomfort or pain was very low in the first few weeks, there were reactions in the following weeks that interfered with patients' daily activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation